Psychoactive Substance Uses and Sexual Behavior - Esmaeil Naseri (روانشناسی بالینی و شخصیت)
Introduction: The relationship between psychoactive substances and sexual behavior is an increasingly important area of research in substance use, primarily due to the prevalence of high-risk sexual behaviors among individuals with substance dependence. The aim of this study was to examine the various relationships between the use of different psychoactive substances and sexual behavior. Method: This study employed a narrative review methodology. To collect data, relevant articles were searched using the keywords  substance use, functions and dysfunctions, sexual behaviors, and  sexual assault. using Google Scholar and PubMed, as well as the NOORMAGS, SID, and Irandoc databases. Results: Behavioral substance use is relatively common. Acute substance use can enhance or improve sexual function and facilitate sexual behavior by reducing inhibitions. Chronic substance use is linked to sexual dysfunctions, such as decreased libido and erectile dysfunction. Additionally, substance use contributes to high-risk sexual behaviors and increases the incidence of sexually transmitted infections (STIs). Substance-facilitated sexual assault is prevalent, yet it is often underreported. Discussion and Conclusions: Evaluating the relationship between substance use and sexual behavior is a crucial component of comprehensive assessment and treatment planning. The clinical benefits of addressing these issues can be substantial, ranging from a reduction in risky sexual behaviors to an enhancement of individuals' quality of life.